Paternal depression in the postnatal period and child development: a prospective population study. - Ramchandani, P; Stein, A; Evans, J; O'Connor, T (2005)
BACKGROUND: Depression is common and frequently affects mothers and fathers of young children. Postnatal depression in mothers affects the quality of maternal care, and can lead to disturbances in their children's social, behavioural, cognitive, and physical development. However, the effect of depression in fathers during the early years of a child's life has received little attention. METHODS: As part of a large, population-based study of childhood, we assessed the presence of depressive symptoms in mothers (n=13,351) and fathers (n=12,884) 8 weeks after the birth of their child with the Edinburgh postnatal depression scale (EPDS). Fathers were reassessed at 21 months. We identified any subsequent development of behavioural and emotional problems in their children (n=10,024) at age 3.5 years with maternal reports on the Rutter revised preschool scales. FINDINGS: Information was available for 8431 fathers, 11,833 mothers, and 10,024 children. Depression in fathers during the postnatal period was associated with adverse emotional and behavioural outcomes in children aged 3.5 years (adjusted odds ratio 2.09, 95% CI 1.42-3.08), and an increased risk of conduct problems in boys (2.66, 1.67-4.25). These effects remained even after controlling for maternal postnatal depression and later paternal depression. INTERPRETATION: Our findings indicate that paternal depression has a specific and persisting detrimental effect on their children's early behavioural and emotional development.